Metallographic Observation for Evaluating Microstructural Evolution on Various Cross-Sections of Forged Part upon Air-Cooling from Finishing Temperature - Jenicek, Stepan; Vorel, Ivan; Kana, Josef (Manufacturing Technology Journal, 2018)
Utility properties of forgings, particularly the mechanical ones, are among the primary aspects of interest to the customers of forge shops. These properties arise from internal structure whose evolution depends predominantly on the combination of parameters of deformation processes applied during forging, on the temperature profile during cooling and on the shape of the forged part. As microstructural evolution depends on the shape of the particular cross section of the forged part, an appreciable inhomogeneity of mechanical properties occurs in forgings. This article deals with observation of microstructural evolution in a chosen forged part, depending on cooling profiles of its various cross sections. The experimental programme of mechanical working and treatment of the forged part was based on the material-technological modelling approach. Microstructural evolution was studied using light and electron microscopic methods. Results of this analysis provided a basis for outlining optimization steps for mechanical working and treatment of the forged part.
Keywords: material-technological modelling; C45; cooling rate; microstructure